(untitled) (Research, Society and Development, 2021)
To demonstrate the efficiency of Bimaxillary Orthognathic Surgery in patients with Obstructive Sleep Apnea Syndrome. To this end, we proceed to the clinical case of a patient with retrognathism, with complaints about difficulties to sleep, night snoring, difficulty breathing and little disposition throughout the day. She also complained about her facial appearance. Through intra-oral, extra-oral clinical examinations and confirmed by imaging exams, it is thus diagnosed as Angle class II. The treatment with orthognathic surgery is pertinent to patients who exhibit facial imperfections, including the teeth and the skeleton of the face. being remedied only with orthodontic treatment. Because the deficiency to be solved is in the jaw and / or maxilla and not only in the dental positioning. Thus, it is observed that the results obtained through surgery with osteotomies and traction myorhaphy of the suprahyoid muscles become efficient. It is concluded that when well planned and indicated, orthognathic surgery does not become an invasive procedure, but effective in the treatment.